2015
DOI: 10.1002/art.38969
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde‐Acetaldehyde Adducts and Anti–Malondialdehyde‐Acetaldehyde Antibodies in Rheumatoid Arthritis

Abstract: Objective As a product of oxidative stress associated with tolerance loss in other disease states, we investigated the presence of malondialdehyde-acetaldehyde (MAA) adducts and circulating anti-MAA antibody in rheumatoid arthritis (RA). Methods Synovial tissues from RA and osteoarthritis patients were examined for the presence of MAA-modified and citrullinated proteins. Anti-MAA antibody isotypes were measured in RA cases (n = 1720) and healthy controls (n = 80) by ELISA. Antigen-specific anti-citrullinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 44 publications
12
155
1
1
Order By: Relevance
“…There is growing awareness that reactive oxygen species and free radicals may play an important role in mediating cellular injury and tissue damage in rheumatoid arthritis. Thiele et al [32] have reported malondialdehyde-acetaldehyde (MAA) adduct formation is increased in RA. They appear to result in robust antibody responses which are strongly associated with anti citrullinated protein antigens (ACPAs) suggesting that MAA formation may be a cofactor that drives tolerance loss, resulting in the autoimmune responses characteristic of RA.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing awareness that reactive oxygen species and free radicals may play an important role in mediating cellular injury and tissue damage in rheumatoid arthritis. Thiele et al [32] have reported malondialdehyde-acetaldehyde (MAA) adduct formation is increased in RA. They appear to result in robust antibody responses which are strongly associated with anti citrullinated protein antigens (ACPAs) suggesting that MAA formation may be a cofactor that drives tolerance loss, resulting in the autoimmune responses characteristic of RA.…”
Section: Resultsmentioning
confidence: 99%
“…These are: i) carbamylation involving the reaction of cyanate present in cigarette smoke with the primary amine group of protein/peptidyl-lysine, resulting in conversion to potentially autoantigenic protein/peptidyl-homocitrulline, which is potentiated by neutrophil/monocyte-derived myeloperoxidase [77]; and ii) ROSmediated lipid peroxidation, resulting in the formation of malondialdehyde and acetaldehyde which, in turn, form potentially autoantigenic protein adducts via reaction with primary amine groups of amino acids [77,78].…”
Section: Pro-inflammatory Effects Of Smokingmentioning
confidence: 99%
“…This extremely stable ring structure, as well as its ability to generate a potent immune response as outlined below, may represent a mechanism through which oxidative stress and free radical formation potentiate inflammation and lead to both subclinical and clinical disease. Recently, it has been demonstrated that the proinflammatory characteristics of MAA-modified proteins are important in other inflammatory diseases, such as connective tissue disorders and abdominal aortic aneurysms [36][37][38]. However, the remainder of this review will focus on the potential role of MAA in the pathogenesis of atherosclerosis.…”
Section: Stable Protein Adductionmentioning
confidence: 99%